Web-based learning a practical guide - Seamon, Mary Ploski 1943- (Gale virtual reference library, 2001)
"A handbook on a specific model of integrating technology into classroom instruction collaboratively. Presents a sequential model that helps teachers work with media specialists to help students achieve their learning goals."--GVRL description.